Moringa oleifera a possible source of biodiesel - Siti Haizum , Abu Hassan (2013)
Biodiesel is an alternative fuel, produced from domestic and renewable resources. It is biodegradable, non-toxic, and essentially free of sulphur and aromatics. Biodiesel is made through a chemical process called transesterification where triglycerides is working as a main component of vegetable oils, react with an alcohol then produce fatty mono-alkyl esters and glycerol. Currently, biodiesel appears to give the best renewable alternatives to petroleum-based diesel fuel, thus this research is to investigate the possibility of promoting Moringa oleifera as a potential source of biodiesel fuel. The objective of this research was to produce biodiesel from Moringa oleifera seeds, to determine the fatty acid composition and to check the physical properties of Moringa oleifera oils. The majority of biodiesel is produced via base-catalyzed transesterification with methanol. Transestrification of Moringa oleifera oil was carried out by a standard procedure employing a 6:1 molar ratio of methanol to vegetable oil using potassium hydroxide (KOH) as a catalyst. The agitation speed was set at 250 rpm for 90 minutes. Based on the result, around 60 ml of biodiesel was produced and tested. The Moringa oleifera methyl esters (MOME) is tested by GCMS to get the fatty acid percentage. For physical properties, the test showed the properties of biodiesel produced with density of 872.7 kg/m3, cetane number of 64.75, cloud point at 10.7 °C, pour point at 6.1 °C and kinematic viscosity of 4.93 mm2/s. The results showed that the properties are accepted within ASTM D6751 and EN 14214